Diagnóstico para la aplicación de normas ISO 9001:2000 - Valverde Estrada, Alejandro Colon (2009)
The project is on the diagnostic for the application of standard ISO 9001:2000 in a cardboard enterprise. Their objective is to identify the critical processes and to carry out the diagnostic on the execution of a System of Management of Quality based on the standard ISO 9001:2000 in the process of production of EMPRESACA. The Reach covers the processes for the production of the corrugated cardboard, the study will be of the Process of Production, from matter cellar it prevails until that of finished product. The prospective results are: The Map of Process Level 0, Level I where it is observed the necessities and expectations, the factory process and the client's satisfaction, the strategic processes, clave and of support; the Map of Process Level II to know the processes related with the factory that include the storage of the matter cellar prevail and of the finished product, the process of Management and Control of Quality. The Map of Process Level III synthesize the form of administer and to Control the Quality of the product. Later on take place the characterization of the critical processes, the evidences and the solutions for the execution of the requirements. take place the steps for the Implementation the System of Management of Quality.